Improving the methane yield of maize straw: Focus on the effects of pretreatment with fungi and their secreted enzymes combined with sodium hydroxide. (February 2018) - Zhao, Xiaoling; Luo, Kai; Zhang, Yue; Zheng, Zehui; Cai, Yafan; Wen, Boting; Cui, Zongjun; Wang, Xiaofen
Graphical abstract: Highlights: The application of fungi and their enzymes in AD are compared for the first time. Methane increased after enzymatic treatment, but decreased after fungal treatment. The simultaneous reduction of DM, cellulose and hemicellulose achieved high methane. Enzyme (T + A) is an environmentally friendly and inexpensive pretreatment agent. Abstract: In order to improve the methane yield, the alkaline and biological pretreatments on anaerobic digestion (AD) were investigated. Three treatments were tested: NaOH, biological (enzyme and fungi), and combined NaOH with biological. The maximum reducing sugar concentrations were obtained using Enzyme T (2.20 mg/mL) on the 6th day. The methane yield of NaOH + Enzyme A was 300.85 mL/g TS, 20.24% higher than the control. Methane yield obtained from Enzyme (T + A) and Enzyme T pretreatments were 277.03 and 273.75 mL/g TS, respectively, which were as effective as 1% NaOH (276.16 mL/g TS) in boosting methane production, and are environmentally friendly and inexpensive biological substitutes. Fungal pretreatment inhibited methane fermentation of maize straw, 15.68% was reduced by T + A compared with the control. The simultaneous reduction of DM, cellulose and hemicellulose achieved high methane yields. This study provides important guidance for the application of enzymes to AD from lignocellulosic agricultural waste.